Identity, ideology and discourse: Classroom spaces for deconstructions and reconstructions - Luck, Jacqueline; Rudman, Sharon (The IIE, 2017)
South African student identity, constructions of the other and experiences in higher education have been the subject of many studies and examine how students are making sense of their past, present and future. Student-led actions have played a leading role in South Africa’s democratisation and their social movements continue to shake their elders out of inertia on issues of inclusion in higher education. In response to concerns of inclusion, this study examined the potential foregrounding of ideology through theory and practicals to uncover the workings of language and discourse. Using a qualitative methodological case study of first-year students, the workings of ideology and discourse are made explicit through lectures, tutorials, individual and multi-lingual group narratives. With this background students are prompted to make explicit, and start critically examining the validity of common assumptions of particular language groups. This study shows that when students are given opportunities to make their assumptions of identities explicit in a safe space, they largely remain reflective of apartheid ideological assumptions. The paper argues that such a first step, of foregrounding assumptions, then creates a basis for class work on ideologies and their workings, thus providing students with tools for critical deconstructions of assumptions.
Keywords: Discourse; Student experience; Higher education; Student identity; Social movements; First year students; Ideology; Assumptions; Critical deconstruction